Reversal to cisplatin sensitivity in recurrent human ovarian cancer cells by NCX-4016, a nitro derivative of aspirin - Bratasz, Anna (National Academy of Sciences, 2006)
Ovarian cancer is a gynecological malignancy that is commonly treated by cytoreductive surgery followed by cisplatin treatment. However, the cisplatin treatment, although successful initially, is not effective in the treatment of the recurrent disease that invariably surfaces within a few months of the initial treatment. The refractory behavior is attributed to the increased levels of cellular thiols apparently caused by the cisplatin treatment. This observation prompted us to choose a cytotoxic drug whose activity is potentiated by cellular thiols with enhanced specificity toward the thiol-rich cisplatin-resistant cells. We used NCX-4016 [2-(acetyloxy)benzoic acid 3-(nitrooxymethyl)phenyl ester], a derivative of aspirin containing a nitro group that releases nitric oxide in a sustained fashion for several hours in cells and in vivo, and we studied its cytotoxic efficacy against human ovarian cancer cells (HOCCs). Cisplatin-sensitive and cisplatin-resistant (CR) HOCCs were treated with 100 μM NCX-4016 for 6 h, and/or 0.5 μg/ml cisplatin for 1 h and assayed for clonogenecity. NCX-4016 significantly reduced the surviving fractions of cisplatin-sensitive (63 ± 6%) and CR (70 ± 10%) HOCCs. NCX-4016 also caused a 50% reduction in the levels of cellular glutathione in CR HOCCs. Treatment of cells with NCX-4016 followed by cisplatin showed a significantly greater extent of toxicity when compared with treatment of cells with NCX-4016 or cisplatin alone. In conclusion, this study showed that NCX-4016 is a potential inhibitor of the proliferation of CR HOCCs and thus might specifically kill cisplatin-refractory cancer cells in patients with recurrent ovarian cancer.